Urban Forests in Florida: Trees Control Stormwater Runoff and Improve Water Quality - Jennifer Seitz; Francisco Escobedo (EDIS)
FOR-184, a 4-page illustrated fact sheet by Jennifer Seitz and Francisco Escobedo, shows how individual trees and urban forest cover assist in maintaining our watershed health, improve water and soil quality, and lower maintenance and construction costs of water storage and treatment systems. Includes references. Published by the UF School of Forest Resources and Conservation, May 2008.